Penyuluhan Gizi Dan Pengukuran Status Gizi Pada Peserta Kuliah Pakar STIKES Persada Nabire - Bau Kanang; Dara Ningrum Supiyani; Irawati (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2024)
Nutritional status according to WHO (World Health Organization) is used as a benchmark in assessing human development and nutritional needs. Nutritional status itself can be defined as a health condition that arises from a balance between nutritional needs and the nutritional intake received. So monitoring nutritional status regularly is important to ensure good and healthy growth. This method is the first step to identify potential health problems such as stunting, wasting and overweight. The assessment is carried out to determine nutritional status by measuring body weight and length/height with a predetermined body mass index and aims to increase knowledge of nutritional science and determine the nutritional status of expert lecture participants, both students, implementing community service. There are 3 stages in implementing this activity, namely: preparation, inspection and implementation. The preparation stages include obtaining permits, field observations, collecting materials and preparing materials as well as coordinating with related parties. The stages of implementing the activities are taking anthropometric measurements, weighing body weight and taking height measurements and the third stage is providing health education regarding human nutrition and accompanied by questions and answers. The results of this service activity from the 30 participants who attended were measurable, there were several participants who were overweight. So it is necessary to increase nutritional knowledge.